Eficiencia en las instituciones de educación superior públicas colombianas: una aplicación del análisis envolvente de datos. (2016)
In this research paper a study about efficiency of public higher education institutions (IES - for its spanish acronym) of Colombia in 2011, was performed using the methodology of data envelopment analysis after Charnes, Cooper and Rhodess model (CCR), Banker, Charnes and Cooper model (BCC) and the Slack Based Measure (SBM) model, oriented to outputs to determine the echnical, purely technical, scale and mixing efficiencies, respectively. The information by which the research was conducted was taken from the databases of the Ministerio de Educación Nacional de Colombia. In the analysis of the results the extent was determined to which the inefficient IES products should be improved and the possible cause of this inefficiency was identified. Also a classification (ranking) of the universities was performed using the super non radial efficiency super SBM model.